Investigating the development of perceptions and behavioural intentions towards people living with HIV (PLHIV) among pre-clinical medical students in the University of Malaya / Calvin Christopher Willims Fernandez - Calvin Christopher, Willims Fernandez (2021)
Since the beginning of the HIV/AIDS epidemic in the 1980s, there has been a high prevalence of stigma and discrimination towards people living with HIV (PLHIV). They manifest in people’s attitudes and behaviour, and in various contexts including education, employment and healthcare. For the latter specifically, stigma-driven behaviours by healthcare practitioners have resulted in poorer health outcomes for PLHIV, where they are humiliated, isolated and in some cases, even refused treatment. This subsequently leads to an increase in mental health issues and other damaging health behaviours among PLHIV. Numerous studies have explored the manifestation of these stigmatizing attitudes and behaviours among healthcare practitioners and why they exist, but there is still room for research to understand how they develop throughout their lives. Hence, this present study was conducted to explore the different perceptions and behavioural intentions that pre-clinical medical students have towards PLHIV and how they develop over time. Understanding how stigma and discrimination develop in these future healthcare practitioners could provide a better insight into what the education and social systems lack when educating the community, especially future doctors, on HIV/AIDS. Maximum variation purposive sampling was carried out to recruit six pre-clinical medical students from the University of Malaya. They then underwent one-on-one, semi-structured interviews between March 2021 and April 2021. Two main themes emerged in this present study: 1) the manifestation of different perceptions and behavioural intentions towards PLHIV at different phases of their lives and 2) the factors that influence the development of perceptions and behavioural intentions towards PLHIV over time. The findings indicate that early life perceptions of PLHIV were inherently negative and iv misinformed due to lack of accurate HIV/AIDS knowledge by teachers and family members, the imposition of misinformed beliefs by different members of the community and the criminalization of at-risk population groups in Malaysia. However, as they transition into medical school, the development of self-awareness and self-initiative to learn about the experiences of PLHIV, having friends who were open to talk about sex, watching media content that was inclusive of PLHIV’s life journey and real-life encounters with PLHIV in medical school changed their perceptions and behavioural intentions towards PLHIV. Through the medical curriculum, the ability to interact with PLHIV and other members of different marginalized groups increased the students’ level of cognitive and affective empathy towards PLHIV. Being involved in HIV awareness programs and using social media to unlearn stigma have also been transformative in changing their view of PLHIV, from being negative to more positive, especially in the context of religion and healthcare. The present study also discovered that mental health training for medical students can also further support efforts to destigmatize HIV/AIDS among future doctors. Future research should explore how these perceptions and behavioural intentions may be similar for students in other allied health courses, and for medical students in smaller universities that may not have infectious disease departments. Keywords: pre-clinical medical students, HIV, AIDS, perceptions, behavioural intentions